Spatial Organization and Molecular Interactions of the Schizosaccharomyces pombe Ccq1–Tpz1–Poz1 Shelterin Complex. Issue 19 (15th September 2017) - Scott, Harry; Kim, Jin-Kwang; Yu, Clinton; Huang, Lan; Qiao, Feng; Taylor, Derek J.
Abstract: The shelterin complex is a macromolecular assembly of proteins that binds to and protects telomeric DNA, which composes the ends of all linear chromosomes. Shelterin proteins prevent chromosome ends from fusing together and from eliciting erroneous induction of DNA damage response pathways. In addition, shelterin proteins play key roles in regulating the recruitment and activation of telomerase, an enzyme that extends telomeric DNA. In fission yeast, Schizosaccharomyces pombe, interactions between the shelterin proteins Ccq1, Tpz1, and Poz1 are important for regulating telomerase-mediated telomere synthesis and thus telomere length homeostasis. Here, we used electron microscopy combined with genetic labeling to define the three-dimensional arrangement of the S. pombe Ccq1–Tpz1–Poz1 (CTP) complex. Crosslinking mass spectrometry was used to identify individual residues that are in proximity to the protein–protein interfaces of the assembled CTP complex. Together, our data provide a first glimpse into the architectural design of the CTP complex and reveals unique interactions that are important in maintaining the S. pombe telomere in a non-extendible state. Graphical Abstract: Highlights: The CTP complex coordinates extension and protection in S. pombe . The CTP complex is a dimer of trimers. 34-Å resolution model of the CTP complex, solved by negative-stain EM. CTP subunit locations described. MICro-MS identifies unique interactions between Ccq1–Poz1 and supports Ccq1 CTD dimerization.